Analysis Of Total Plate Count, Contamination Of Salmonella, Staphylococcus Aureus, And Escherichia Coli Bacteria In Fish Shredded - Lutfi Maulana; Syahrizal Nasution; Retno Koostati (UNIVED Press, Dehasen University Bengkulu, 2022)
Catfish shredded has become one of the famous foods for many people due to it has a delicious taste and long-life storage of approximately 6-12 months in good storage condition. However, catfish shredded can still be contaminated with pathogenic bacteria that can be causing a healthy problem. Several bacteria that commonly appear in the shredded product are Salmonella, Staphylococcus aureus, and Escherichia coli thus its product need for assessing microbial contamination to ensure product safeties that will be supplied in the community. The microbial contamination assessment method in this research using Indonesian national standardization 2332.1:2015 for Escherichia coli assessment, 2332.2: 2006 for Salmonella assessment, 2332.3:2015 for total plate count assessment, and 2332.9:2015 for Staphylococcus aureus assessment. The catfish shredded sample that is used in this research was obtained from the Regional Technical Implementation Unit Application of Fishery Product Quality, Lampung. The result of the total plate count assessment on this research reported that all of the samples have a total amount of microbes lower than the maximum limit for the fish shredded product. Furthermore, the result also shows that all of the samples are negative from Salmonella, S. aureus, and Escherichia coli. According to Indonesian National Standardization number 7690.1:2013 about the standard of shredded products, all of the samples are appropriate and categorized as a safety product to consume based-on microbial contamination aspect.